EDHF: spreading the influence of the endothelium. - Garland, C; Hiley, C; Dora, K (2011)
Our view of the endothelium was transformed around 30 years ago, from one of an inert barrier to that of a key endocrine organ central to cardiovascular function. This dramatic change followed the discoveries that endothelial cells (ECs) elaborate the vasodilators prostacyclin and nitric oxide. The key to these discoveries was the use of the quintessentially pharmacological technique of bioassay. Bioassay also revealed endothelium-derived hyperpolarizing factor (EDHF), particularly important in small arteries and influencing blood pressure and flow distribution. The basic idea of EDHF as a diffusible factor causing smooth muscle hyperpolarization (and thus vasodilatation) has evolved into one of a complex pathway activated by endothelial Ca(2+) opening two Ca(2+) -sensitive K(+) -channels, K(Ca)2.3 and K(Ca)3.1. Combined application of apamin and charybdotoxin blocked EDHF responses, revealing the critical role of these channels as iberiotoxin was unable to substitute for charybdotoxin. We showed these channels are arranged in endothelial microdomains, particularly within projections towards the adjacent smooth muscle, and close to interendothelial gap junctions. Activation of K(Ca) channels hyperpolarizes ECs, and K(+) efflux through them can act as a diffusible 'EDHF' stimulating Na(+) /K(+) -ATPase and inwardly rectifying K-channels. In parallel, hyperpolarizing current can spread from the endothelium to the smooth muscle through myoendothelial gap junctions upon endothelial projections. The resulting radial hyperpolarization mobilized by EDHF is complemented by spread of hyperpolarization along arteries and arterioles, effecting distant dilatation dependent on the endothelium. So the complexity of the endothelium still continues to amaze and, as knowledge evolves, provides considerable potential for novel approaches to modulate blood pressure.